Microwave Assistant Synthesis and Biological Activity of Some 2,4-Dichloroaryloxyacetyl hydrazones - XIAO, SHAN-MEI (Asian Journal of Chemistry, 2010)
A series of 2,4-dichloroaryloxyacetyl hydrazones was synthesized from 2,4-dichlorophenol under microwave irradiation. Nine 2,4- dichloroaryloxyacetyl hydrazones were synthesized in excellent yields (83-94 %) and short reaction times. The fungicidal activities of some of these compounds were also investigated. The bioassay results indicated that some of these compound exhibit moderate fungicidal activities.